2006
DOI: 10.1309/h5uw6cpcwwc92241
|View full text |Cite
|
Sign up to set email alerts
|

Significance of EGFR Protein Expression and Gene Amplification in Non–Small Cell Lung Carcinoma

Abstract: We evaluated epidermal growth factor receptor (EGFR) protein expression by immunohistochemical analysis and EGFR gene amplification by fluorescence in situ hybridization in 199 consecutive newly diagnosed and surgically treated patients with primary non-small cell lung carcinoma (NSCLC) and correlated results with clinicopathologic findings. EGFR protein expression was more common in squamous cell carcinoma (SCC; 17 [26.2%]) than in adenocarcinoma (14 [11.1%]; (P = .0076) and more frequently associated with EG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
54
4
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(70 citation statements)
references
References 24 publications
10
54
4
1
Order By: Relevance
“…[27][28][29] Although no amplification of EGFR was identified, copy gains of EGFR gene occurred in a quarter of our cases secondarily to polysomy of chromosome 7. This alteration was twice as common in adenoid cystic carcinomas compared to mucoepidermoid carcinomas.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…[27][28][29] Although no amplification of EGFR was identified, copy gains of EGFR gene occurred in a quarter of our cases secondarily to polysomy of chromosome 7. This alteration was twice as common in adenoid cystic carcinomas compared to mucoepidermoid carcinomas.…”
Section: Discussionmentioning
confidence: 53%
“…Indeed, although one study reported no significant prognostic value, 40 increased EGFR gene and chromosome 7 copy numbers were reportedly associated with poor tumor differentiation but were less frequent in T4 compared to T1 tumors. 28 Also, increased EGFR gene and chromosome 7 copy numbers tended to be less frequent in tumors with lymph node metastasis. 28 These results would suggest that chromosome 7 polysomy is associated with lower stage disease, a similar finding to our study, although limited by the small number of cases.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Several protein and molecular studies have shown that EGFR expression is related to the gene amplification mechanism, but the role of chromosome 7 multiplication is under consideration (33). The significance of the assessment of EGFR gene copy number and EGFR protein expression as biomarkers to predict therapy responders as well as the selection of patients who might potentially benefit from EGFR targeted therapies was demonstrated by different studies (34,35). In fact, data for the relationship between EGFR expression on the protein level and response to EGFR specific therapies is inconsistent (36).…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between levels of EGFR and treatment effectiveness is debated. Reports of EGFR as a prognostic factor showed disparate results, though for some tumors, EGFR is a good indicator of reduced survival rates in more aggressive disease (Dacic et al, 2006).…”
Section: Introductionmentioning
confidence: 99%